Seismic Resistance and Performance Evaluation of Masonry Dwellings After the February 6, 2023, Kahramanmaraş Earthquake Sequence in Türkiye - Onat, Onur; Yon, Burak; Uslu, Ali; Oncu, Mehmet Emin; Varolgunes, Sadik; Karasin, Ibrahim Baran; Gor, Mesut (World Scientific Publ Co Pte Ltd, 2024)
On February 6, 2023, two catastrophic earthquakes occurred on the East Anatolian Fault. The earthquakes had magnitudes of Mw = 7.7 and 7.6 and struck Kahramanmara & scedil;-Pazarc & imath;k and Kahramanmara & scedil;-Elbistan, respectively. The Kahramanmara & scedil;-Pazarc & imath;k earthquake was triggered at 04:17 local time on the Dead Sea Fault (a branch of the East Anatolian Fault). The last earthquake on the addressed fault occurred about 500 years ago. The recorded peak ground acceleration (PGA) at the Pazarc & imath;k station reached 2.05g. In addition, the Pazarc & imath;k earthquake triggered two independent earthquakes, the Nurda & gbreve;& imath; and Islahiye earthquakes, which occurred 10 min later than the Pazarc & imath;k earthquake. However, the last earthquake, with its epicenter in Kahramanmara & scedil;-Elbistan, struck at 13:24 local time. The recorded PGA for the Elbistan earthquake is 0.68g. This study aims to present the fault rupture mechanism of the February 6, 2023, Kahramanmara & scedil; earthquakes, earthquake characteristics, and to evaluate the performance of masonry dwellings during the Kahramanmara & scedil; earthquake doublet, which affected 10 provinces and numerous towns and villages. This paper also aims to illustrate the damage and failure mechanisms of the masonry dwellings, despite unexpectedly high accelerations that exceeded the design spectrum in the field, specifically in Kahramanmara & scedil;, Gaziantep, Hatay, and Malatya, according to the current earthquake code in use.
Keywords: Kahramanmara & scedil; earthquakes; East Anatolian Fault; masonry dwellings; seismic structural performance